8 Adverse cardiovascular outcomes in diabetic patients with heart failure are mediated by silent myocardial infarction. (28th January 2023) - Sharrack, Noor; Brown, Louise AE; Farley, Jonathan; Wahab, Ali; Jex, Nicholas; Thirunavukarasu, Sharmaine; Chowdhary, Amrit; Gorecka, Miroslawa; Javed, Wasim; Xue, Hui; Levelt, Eylem; Dall'Armellin, Erica; et al.
Abstract : Introduction: Diabetic patients with heart failure (HF) have worse outcomes compared to normoglycaemic HF patients. 1 2 Patients with diabetes mellitus (DM) are at increased risk of ischaemic heart disease (IHD), silent myocardial infarction (MI) and coronary microvascular dysfunction (CMD). 3 All of these can be assessed and quantified using cardiac magnetic resonance (CMR), including most recently quantitative myocardial blood flow (MBF). We aimed to investigate whether outcomes in diabetic HF patients without known IHD are mediated by silent MI or CMD. Materials and Methods: Prospectively recruited outpatients with a recent diagnosis of HF underwent perfusion CMR (3T Siemens Prisma) for calculation of myocardial perfusion reserve (MPR) using the technique described. 4 All patients were divided into groups depending on their HbA1c level or a known diagnosis of DM (normoglycaemia, pre-diabetes and diabetes). Exclusion criteria included anginal chest pain or history of IHD. Silent IHD was defined as inducible ischaemia or MI on CMR. Patients were followed up (median 3.0 years) for major adverse cardiovascular events (MACE). Results: Final analysis included 343 patients (176 normoglycaemic, 84 pre-diabetic and 83 diabetic). The prevalence of silent IHD, was highest in diabetic patients (31.3%) compared to prediabetic patients (20.2%) and normoglycaemic patients (17.0%, P=0.03). Stress MBF was lowest in diabetic patients (1.93±0.62) then prediabetic patients (1.59±0.54) then normoglycaemic patients (1.53±0.52, P<0.001 for trend). MPR was not significantly different between groups. During follow up 45 patients suffered at least one MACE event. On univariate Cox regression analysis, a diagnosis of DM was associated with increased risk of MACE ([HR] 1.95 [1.07–3.55 95% CI]). In diabetic patients, MACE was associated with LVEF, RVEF, rest MBF, MPR, native T1 and silent IHD. After stepwise Cox regression only RVEF, rest MBF and silent IHD, but not MPR, were associated with MACE. Discussion: Diabetic patients with HF and no history or symptoms of IHD had worse outcomes than their non-diabetic counterparts which was associated with silent IHD but not CMD. Conclusion: Silent MI in diabetic HF patients is an important contributor to adverse cardiovascular outcomes. Acknowledgements: The authors thank the clinical staff of the CMR department, and the National Institute of Health Research nurses based at Leeds General Infirmary. References: Shah AD, Langenberg C, Rapsomaniki E, et al . Type 2 diabetes and incidence of cardiovascular diseases: a cohort study in 1.9 million people. Lancet Diabetes Endocrinol 2015;3 :105–13. Cubbon RM, Adams B, Rajwani A, et al . Diabetes mellitus is associated with adverse prognosis in chronic heart failure of ischaemic and non-ischaemic aetiology. Diab Vasc Dis Res 2013;10 :330–6. Schlesinger S, Neuenschwander M, Barbaresko J, et al . Prediabetes and risk of mortality, diabetes-related complications and comorbidities: umbrella review of meta-analyses of prospective studies. Diabetologia 2022;65 :275–285. Kellman P, Hansen MS, Nielles-Vallespin S, et al . Myocardial perfusion cardiovascular magnetic resonance: optimized dual sequence and reconstruction for quantification. J Cardiovasc Magn Reson 2017;19 :43.